Perceiving and attributing intentionality in schizophrenia. Issue 4 (3rd July 2020) - Langdon, Robyn; Boulton, Kelsie; Connaughton, Emily; Gao, Tao
ABSTRACT: Introduction: People with schizophrenia perform poorly on theory-of-mind (ToM) tasks. They also generate less mental-state language to describe test stimuli depicting intentionality. Some of these individuals also show excessive mentalising when objective cues of intentionality are absent. We tested perceiving and attributing intentionality to resolve this paradox. Methods: 23 schizophrenia patients and 20 healthy controls completed the chasing detection task to assess perceptual sensitivity to cues of intentionality. Other tasks assessed spontaneous attributions of intentionality (irrespective of accuracy) and accurate ToM inferences. Results: Perceptual sensitivity to cues of intentionality did not differ between groups. Patients were less likely to spontaneously attribute intentionality (irrespective of accuracy) or perform ToM tasks accurately. Chasing-detection response bias, but not perceptual sensitivity, correlated with attributions of intentionality. Referential (and to less extent) persecutory ideation associated with excessive mentalising when cues of intentionality were absent. Conclusions: Intentionality can be directly perceived, independent of attributions or inferences, in people with schizophrenia. We conclude that the flow of information from intact perceptual detection to evoke spontaneous attributions of intentionality is disrupted in schizophrenia, with flow-on detrimental effects on accurate ToM reasoning. Referential/persecutory ideation motivates inappropriate mentalising when objective cues of intentionality are absent.